2012
DOI: 10.5194/bg-9-4247-2012
|View full text |Cite
|
Sign up to set email alerts
|

Measuring the biosphere-atmosphere exchange of total reactive nitrogen by eddy covariance

Abstract: Abstract. The (net) exchange of reactive nitrogen (N r ) with the atmosphere is an important driver for ecosystem productivity and greenhouse gas exchange. The exchange of airborne N r includes various trace compounds that usually require different specific measurement techniques, and up to now fast response instruments suitable for eddy covariance measurements are only available for few of these compounds.Here we present eddy covariance flux measurements with a recently introduced converter (TRANC) for the su… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
58
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(59 citation statements)
references
References 53 publications
1
58
0
Order By: Relevance
“…Using the H 2 O flux data again an estimate of the correction term can be made. Like the WPL correction, this estimated correction term reaches an absolute maximum during the daytime (0.79 and 0.67 ppt m s −1 on average), about 4-5 times larger than the estimated WPL correction term (consistent with what was found by Ammann et al, 2012). It can therefore become important (> 5 % of the calculated flux); if only the fluxes above the detection limit are considered, about 12 % of the data have correction terms greater than 5 %.…”
Section: Flux Interferencessupporting
confidence: 78%
See 1 more Smart Citation
“…Using the H 2 O flux data again an estimate of the correction term can be made. Like the WPL correction, this estimated correction term reaches an absolute maximum during the daytime (0.79 and 0.67 ppt m s −1 on average), about 4-5 times larger than the estimated WPL correction term (consistent with what was found by Ammann et al, 2012). It can therefore become important (> 5 % of the calculated flux); if only the fluxes above the detection limit are considered, about 12 % of the data have correction terms greater than 5 %.…”
Section: Flux Interferencessupporting
confidence: 78%
“…When the correction term approaches 10 %, the fluxes were almost always below the detection limit (discussed below). As pointed out by Ammann et al (2012), the chemiluminescent reaction on which the detection of reactive nitrogen oxides is based is sensitive to water vapour, which acts as a quencher and could therefore also lead to an artificial component of the flux. Previous lab studies with the instrument used here showed a linear reduction in sensitivity of about 0.6 and 0.7 % per g m −3 of water vapour increase in channel 1 and channel 2 respectively.…”
Section: Flux Interferencesmentioning
confidence: 99%
“…Other arising problems when using long tubing such as the correct determination of the lag time (to maximise the covariance), i.e. the time the air sample needs from entering the converter until it reaches the analyser, or possible high-frequency damping will be addressed in Ammann et al (2012).…”
Section: Discussionmentioning
confidence: 99%
“…The purpose of this paper is the presentation of the converter, its characteristics and results of performance tests. Validation and long-term application of the converter for EC flux measurements is presented in companion papers by Ammann et al (2012) and Brümmer et al (2012b).…”
Section: Motivation and Objectives Of Present Studymentioning
confidence: 99%
“…In the future, COS measurements may lead to a better understanding of both ecosystem carbon cycling and ecosystem sulfur cycling (Kesselmeier et al, 1999;Billesbach et al, 2014). In addition to COS studies that aimed at measuring other compounds such as ozone (O 3 ) and reactive components as part of nitrogen cycling (NO x , which is the sum of NO and NO 2 ; NO y , which is the total of NO x plus additional products of atmospheric oxidation of NO x , namely HNO 3 , HONO, NO 3 , N 2 O 5 , HNO 4 , PAN, RONO 2 , and ROONO 2 ; and ammonia, NH 3 ) with micrometeorological approaches have become available in the past decades (Munger et al, 1996;Eugster and Hesterberg, 1996;Hesterberg et al, 1996;Munger et al, 1998;Famulari et al, 2004;Horii et al, 2004;Jones et al, 2011;Ferrara et al, 2012;Ammann et al, 2012;Marr et al, 2013;Geddes and Murphy, 2014). In particular, the ongoing development of easyto-deploy quantum cascade laser spectrometers capable of measuring various scalars in the field opened the door for fast-response concentration measurements (Bruemmer et al, 2013;Famulari et al, 2004;Skiba et al, 2009;Sutton et al, 2007).…”
Section: Future Directions and Challengesmentioning
confidence: 99%